Agriculture and Food in Pre-Hispanic Mexico and the 16th Century - Sánchez Verín, Carlos Arturo Giordano (Geografares, 2018)
The emergence of agriculture in Mexico was a factor of great relevance, which allowed the development of Mesoamerican cultures more than three thousand years of history. The geographical location of the different ethnic groups that inhabited this region allowed the cultivation of a wide variety of plants, such as corn, beans, pumpkin and chili, basic products in the Mesoamerican diet, as well as other products were developed according to the geographic characteristics and climatological, such as cocoa, from which chocolate is obtained, and even vanilla, being appreciated all over the world. Those original products were mixed with those brought by Europeans in the sixteenth century and this gave rise to Mexican cuisine, which in 2010 was declared an Intangible Cultural Heritage of Humanity by the United Nations Educational, Scientific and Cultural Organization (UNESCO).Keywords: Mesoamerican cultures, Mexican gastronomy, Intangible Cultural Heritage of Humanity of the United Nations Educational, Scientific and Cultural Organization (UNESCO)